A brief mindfulness-based intervention (bMBI) to reduce teacher stress and burnout. (April 2021) - Taylor, Stephen G.; Roberts, Alex M.; Zarrett, Nicole
Abstract: Teacher stress and burnout contribute to attrition and stress-related health concerns. Despite some positive effects, previous mindfulness-based interventions (MBI) have failed to incorporate key elements of methodological rigor and have included large dosages despite research suggesting that such dosages are iatrogenic. The current study demonstrates the efficacy of a brief MBI (bMBI; four sessions, six total hours) to reduce self-reported stress, burnout, and depression, and suggests the bMBI can protect against deleterious impacts to physiological functioning. The study informs the design and implementation of future MBIs, including strategies for reducing intervention dosages, in order to improve effectiveness and maximize cost-effectiveness. Highlights: Mindfulness-based interventions have the potential to combat teacher stress and burnout. However, interventions with large dosages have had iatrogenic effects. The current study tests the efficacy of a brief mindfulness-based intervention. Significant positive intervention effects were found for stress, burnout, and depression. Findings support the development of briefer designs to improve efficacy and cost-effectiveness.